Modulation of Human Valve Interstitial Cell Phenotype and Function Using a Fibroblast Growth Factor 2 Formulation - Najma Latif (250130) (2015)
Valve interstitial cells (VICs) are fibroblastic in nature however in culture it is widely accepted that they differentiate into a myofibroblastic phenotype. This study assessed a fibroblast culture media formulation for its ability to maintain the phenotype and function of VICs as in the intact healthy valve. Normal human VICs were cultured separately in standard DMEM and in fibroblast media consisting of FGF2 (10ng/ml), insulin (50ng/ml) and 2% FCS for at least a week. Cell morphology, aspect ratio, size, levels and distribution of protein expression, proliferation, cell cycle, contraction and migration were assessed. Some VICs and some valve endothelial cells expressed FGF2 in valve tissue and this expression was increased in calcified valves. VICs in DMEM exhibited large, spread cells whereas VICs in fibroblast media were smaller, elongated and spindly. Aspect ratio and size were both significantly higher in DMEM (p<0.01). The level of expression of α-SMA was significantly reduced in fibroblast media at day 2 after isolation (p<0.01) and the expression of α-SMA, SM22 and EDA-fibronectin was significantly reduced in fibroblast media at days 7 and 12 post-isolation (p<0.01). Expression of cytoskeletal proteins, bone marker proteins and extracellular matrix proteins was reduced in fibroblast media. Proliferation of VICs in fibroblast media was significantly reduced at weeks 1 (p<0.05) and 2 (p<0.01). Collagen gel contraction was significantly reduced in fibroblast media (p<0.05). VICs were found to have significantly fewer and smaller focal adhesions in fibroblast media (p<0.01) with significantly fewer supermature focal adhesions in fibroblast media (p<0.001). Ultrastructurally, VICs in fibroblast media resembled native VICs from intact valves. VICs in fibroblast media demonstrated a slower migratory ability after wounding at 72 hours (p<0.01). Treatment of human VICs with this fibroblast media formulation has the ability to maintain and to dedifferentiate the VICs back to a fibroblastic phenotype with phenotypic and functional characteristics ascribed to cells in the intact valve. This methodology is fundamental in the study of normal valve biology, pathology and in the field of tissue engineering. Other Information Published in: PLOS ONE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1371/journal.pone.0127844 Additional institutions affiliated with: Qatar Cardiovascular Research Centre